PEMELIHARAAN IKAN PATIN SIAM (Pangasius hypopthalmus) DENGAN SISTEM RESIRKULASI PADA WADAH DENGAN BENTUK YANG BERBEDA - Pasaribu, Bora Marissa; Tang, Usman M.; ', Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from May to June 2017 for 45 days in HatcheryTIU (Technical Implementation Unit) of Marine and Fisheries Faculty, University ofRiau. The aims of this study were to determine the growth and survival rate of Siamesecatfish which were reared on different shape of the tanks. The tanks were made oftarpaulin plastic material with 30 L of water volume capacity. Stocking density ofexperimental fishes were 30 fishes/tank. The method of the study was an experimentalmethod with 4 treatments and 3 replications. The treatments were: P1 = circle shape, P2 =Square-shape, P3 = Octagonal shape, P4 = Triangular shape, and P5 = Rectangularshaped. The result of this study can be concluded that different shape of tanks have nosignificant effect on growth and survival rate performance of the Siamese catfish fries.The growth performance of round, square, octagonal, triangle and rectangular shape oftanks respectively has given an absolute weight growth of 5.93 g; 6.00 g; 6.18 g; 5.72 gand 5.77 g, then an absolute length growth were 4.88 cm; 4.93 cm; 4.91 cm; 4.76 cm and4.85 cm, a daily growth rate 4.24%, 4.32%, 4.27%, 4.21% and 4.24, the food efficiency92.67%, 92.63% , 94.31%, 92.42% and 91.23% and the survival rate 100%, 97.8%,100%, 98.9% and 100% respectively. The result of water quality measurement which isstill in the optimal range for rearing the Siamese catfish where the temperature was 28-30° C, 5-6 of pH, 5-6 mg/L of DO, 0,03-0,05 mg / L of Ammonia, 0,17-0,20 mg / L ofNitrite, and Nitrate was 0.80-0.98 mg / L.Keywords : Pangasius hypopthalmus, recirculation system, different shape of tanksurvival rate